Exploratory investigation on antibodies to GluN1 and cognitive dysfunction in patients with chronic autoimmune psychosis. (19th January 2021) - Abe, Kie; Chiba, Yuhei; Katsuse, Omi; Takahashi, Yukitoshi; Suda, Akira; Hattori, Saki; Yoshimi, Ryusuke; Kirino, Yohei; Kunii, Misako; Yoshimi, Asuka; Asami, Takeshi; Hishimoto, Akitoyo
Highlights: Cognitive dysfunction underlies psychiatric symptoms in autoimmune psychosis (AP). Relationships between 3 serum antibodies and cognitive dysfunction were investigated. Anti-GluN1-NT antibody titers correlated with working memory. Anti-NMDAR and anti-thyroid antibodies did not correlate with cognitive dysfunction. Anti-GluN1-NT antibody might be a biomarker for cognitive dysfunction in chronic AP. Abstract: Introduction: Mild cognitive dysfunction has been implicated in a number of psychiatric diseases and affects social functioning. Although clinical criteria were recently proposed for autoimmune psychosis (AP), biomarkers have not yet been established for the severity and prognosis of cognitive dysfunction. We herein investigated the relationships between 3 types of serum antibodies and cognitive dysfunction in chronic psychiatric patients suspected of AP. Methods: We included 31 patients suspected of AP and obtained information on their clinical characteristics. Three types of autoantibodies (the anti -N- methyl-D -aspartate receptor (anti-NMDAR Ab), anti- N -terminal of GluN1 (anti-GluN1-NT Ab), and anti-thyroid antibodies) were evaluated in serum. Cognitive function was assessed using Wechsler Adult Intelligence Scale-III. We examined the relationships between serum autoantibodies and cognitive dysfunction in patients using multiple regression models. Results: Serum titers of anti-GluN1-NT Ab significantly contributed to the estimated score of working memory ( B = -55.85, β = -0.46, p = 0.01), while no correlation was observed between the other 2 types of antibodies and cognitive function. Conclusions: The present results indicate the potential of serum anti-GluN1-NT Ab as a biomarker for the severity and prognosis of cognitive dysfunction underlying various psychiatric symptoms in patients with AP. The pathological significance of anti-GluN1-NT Ab needs to be verified in future studies.